Effects of an orthogonal magnetic field on discharge craters created during the single-spark electrical discharge machining process - JIA Jian-yu; WANG Yan-qing; YANG Sheng-qiang; LI Wen-hui (工程科学学报)
In the single-spark electrical discharge machining (EDM) process under the action of an orthogonal magnetic field, the plasma from the electric discharge is deflected and extends to the direction of the Lorenz force, which leads to a change in the discharge craters compared with traditional EDM. In this paper, the morphology and characteristics of craters created during the process of magnetic field assisted electrical discharge machining (MF-EDM) were studied. The results of this study may be applied to production practice, and it is expected that the machining of tapered holes can be realized using magnetic field assisted EDM. Based on single-pulse MF-EDM in gas, the crater morphology was observed using a surface topography instrument. During the experiment the voltage waveform was obtained using an oscilloscope and the current waveform was calculated using the simulation software SABER. After measuring the distribution of the orthogonal magnetic field, the ampere force of the electrode at the moment of discharge was calculated. The deformation of the end of the electrode was obtained using simulation software ANSYS15.0. The offset of the starting point of the discharge under the influence of the orthogonal magnetic field was proven. Then, rules for the effects of the magnetic field and discharge parameters on the craters were obtained. The results indicate that crater length increases with an increase in magnetic field intensity and open circuit voltage, but the influence of the electrode overhang length shows the opposite. There is no obvious change rule for crater depth with an increase in magnetic field intensity, open circuit voltage, or electrode overhang length. To obtain the maximum length or minimum depth of the crater, an optimum combination of the capacitance and magnetic field intensity can be used. With an increase in magnetic induction intensity and discharge energy, the offset of the discharge point increases.